Influence of combined mechanical-chemical versus mechanical bowel preparation on anastomotic leak and surgical site infections after elective resection of left colon cancer - Ali, Mohamed Mahmoud; El-Badry, Ashraf Mohammad (International Surgery Journal, 2020)
Background: Mechanical bowel preparation (MBP) before elective resection of left colon cancer remains controversial. We propose that the protective effect of MBP is dependent on its combination with chemical preparation by oral antibiotics. Methods: Medical data of adult patients with left colon cancer who underwent elective resection at Sohag University Hospital (August 2016-March 2019) were reviewed. Anastomotic leak (AL), surgical site infections (SSI), postoperative morbidity and mortality were compared among patients who preoperatively received MBP followed by chemical preparation with oral antibiotics (MBP and OABx group) versus another group of preoperative MPB alone (MBP group). Results: Forty-two patients with left colon adenocarcinoma were enrolled, 21 per group. Overall, sigmoid colon was the most common site of left sided colon cancer (76%). Malignant lesions were found in proximal sigmoid in 19 (45%), rectosigmoid in 13 (31%), descending colon in 8 (19%) and splenic flexure in 2 (5%) patients. Dukes’ classification was A in 6 (14%), B in 19 (45%) and C in 17 (41%) patients. Compared with MBP, MBP and OABx group showed significantly lower rates of anastomotic leak (3 patients (14%) versus 1 (5%) respectively, p<0.05) and surgical site and intraabdominal infections (7 patients (33%) versus 2 (10%), p<0.05). MBP and OABx group exhibited lesser grades of postoperative complications (p<0.05) and shorter hospital stay (p<0.05). Postoperative mortality occurred only in the MBP group. Conclusions: Combined mechanical-chemical bowel preparation prior to elective resection of left colon cancer confers superior clinical outcome regarding anastomotic leak, surgical site infections and overall postoperative complications.